SKILLS-BASED NON-FORMAL EDUCATION IN WOMEN'S EMPOWERMENT: A CASE STUDY OF THE SAMARINDA WEAVING COMMUNITY: Pendidikan Nonformal Berbasis Keterampilan dalam Pemberdayaan Perempuan: Studi Kasus Komunitas Tenun Samarinda - ismaya nurhayati nurhayati; Muhamad Ali Salman; Hepy Triwinarti; Arif Sugianto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to examine the implementation of skills-based non-formal education in efforts to empower women through activities in the Samarinda Weaving Community by using a qualitative approach of case study methods. The research subjects included community managers, artisans, and instructors, with data collection techniques in the form of in-depth interviews, observations, and documentation studies, which were then analyzed using the Miles and Huberman interactive model. The results of the study show that non-formal education activities include weaving training from the introduction stage of tools and materials, learning basic techniques, developing distinctive motifs, production management, to product marketing which is carried out through the learning by doing method and a community-based continuous learning system. The program contributes to improving technical skills, expanding women's access to productive resources, strengthening decision-making capacity, increasing income and economic independence, and active participation in social activities and preserving local culture through traditional weaving motifs and techniques. Of the total of about 30 active artisans, more than 60% are now major contributors to family income and 40% of participants have played a role in social activities at the RT, sub-district, and sub-district levels, including as PKK administrators, training facilitators, and cultural event committees. However, this program still faces obstacles in the form of high raw materials, limited tools, and lack of regeneration of young artisans. In conclusion, skills-based non-formal education has an important role in women's empowerment, so synergy between stakeholders, strengthening digital literacy, and regeneration strategies is needed to strengthen the sustainability and development of programs in the future.